2016
DOI: 10.1186/s12348-016-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal dexamethasone implant for the treatment of cystoid macular oedema associated with acute retinal necrosis

Abstract: BackgroundAcute retinal necrosis is a rare but devastating ocular condition. We report two cases of acute retinal necrosis in immunocompetent patients, complicated by cystoid macular oedema and treated with intravitreal dexamethasone (OZURDEX®) implant.ResultsTwo patients diagnosed with acute retinal necrosis were treated with intravenous acyclovir. Both of them developed cystoid macular oedema following resolution of viral retinitis. Ocular condition of the first patient was further complicated by central ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The intravitreal DEX implant has been successfully employed in patients with infectious uveitis, though the presence of intraocular infection represents a formal contraindication (Table 3) [118][119][120][121][122][123]. Intravitreal Dex should not be advocated as a primary treatment option in patients with infectious uveitis, however it could represent a useful and minimally invasive therapeutic resource in carefully selected cases.…”
Section: Evidence Of the Efficacy Of Dex In Other Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intravitreal DEX implant has been successfully employed in patients with infectious uveitis, though the presence of intraocular infection represents a formal contraindication (Table 3) [118][119][120][121][122][123]. Intravitreal Dex should not be advocated as a primary treatment option in patients with infectious uveitis, however it could represent a useful and minimally invasive therapeutic resource in carefully selected cases.…”
Section: Evidence Of the Efficacy Of Dex In Other Conditionsmentioning
confidence: 99%
“…The intravitreal DEX implant has been successfully employed in patients with infectious uveitis, though the presence of intraocular infection represents a formal contraindication ( Table 3 ) [ 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Dex Implant In Other Conditionsmentioning
confidence: 99%
“…Systemic administration is often favoured as it is easily ceased should there be clinical deterioration. Promising results with cautious use of local injected corticosteroid together with systemic antiviral cover have recently been reported, however this remains unconventional …”
Section: Treatmentmentioning
confidence: 99%
“…Promising results with cautious use of local injected corticosteroid together with systemic antiviral cover have recently been reported, however this remains unconventional. [69][70][71] Aggressive antiviral therapy has improved visual outcomes after ARN. Rates of severe vision loss to < 6/60 were 76% in the pre-antiviral era as compared to 50% thereafter.…”
Section: Acute Retinal Necrosismentioning
confidence: 99%
“…Etiologic confirmation via intraocular fluid analysis has shown that varicella zoster virus (VZV), herpes simplex virus (HSV) type-1 and -2, cytomegalovirus (CMV), and Epstein-Barr virus (EBV) are related to the pathogenesis of ARN [10,11]. It is widely known that iatrogenesis immunosuppression associated with subtenonial or intravitreal corticosteroids may predispose patients to ARN, and several reports of ARN have shown its relation to intravitreal Ozurdex® injection [12][13][14]. Here, we report a case of intravitreal Ozurdex® injection-related ARN in an immunocompetent patient with RVO.…”
Section: Introductionmentioning
confidence: 99%